Berisiko Tinggi Titik Masuk Hewan Pembawa Rabies di Kabupaten Sumbawa dan Dompu, Provinsi Nusa Tenggara Barat - Nurjumaatun, Nurjumaatun; Pribadi, Eko Sugeng; Poetri, Okti Nadia (Jurnal Veteriner, 2023)
Rabies is a zoonosis caused by infection of Lyssavirus belong to Rhabdoviridae family. Dompu and Sumbawa District, which are located on Sumbawa Island, West Nusa Tenggara Province, were designated as rabies outbreak in 2019. This study was aim to qualitatively estimate the magnitude of the risk of rabies-carrying animals (RCA) entry at each entry point for RCA to Sumbawa and Dompu Regencies, NTB Province. The risk assessment was carried out following risk analysis guidelines of the United NationsWorld Organization forAnimal Health (World Organization for Animal Health, Office Internationale de Epizootic, OIE), and referring to Australian Biosecurity methods. The uncertainty assessment refers to the European Food Safety Authority (EFSA). The results showed that the entry points were in Lunyuk sub-District, Sumbawa sub-District, Labuhan Badas sub-District, Moyo Hilir sub-District, Moyo Hulu sub-District, Unter Iwes sub-District in Sumbawa District, and Pekat sub-District, Kempo sub-District, Manggelewa sub-District, Hu’u subDistrict and Woja sub-Districts in Dompu District. Based on the research results, it can be concluded that rabies-carrying animals entry points in NTB Province are classified as high risk. The high risk at rabies-carrying animals entry points is due to the lack of public awareness and knowledge about rabies.